2022
DOI: 10.1007/s42532-022-00132-8
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda

Abstract: Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…According to M. Eaton et al (2022), when revising this research agenda, it is essential to focus on how language can be used effectively to break down barriers, increase understanding, and foster the mutual understanding that is needed for theory, practice, and policy to come together and implement ecological solutions. Researchers and stakeholders can improve their interactions by learning to interpret, organize, and negotiate language and frames; this, in turn, can lead to better solutions through alternate communication methods and transformational learning.…”
Section: Importance Of Language In International Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to M. Eaton et al (2022), when revising this research agenda, it is essential to focus on how language can be used effectively to break down barriers, increase understanding, and foster the mutual understanding that is needed for theory, practice, and policy to come together and implement ecological solutions. Researchers and stakeholders can improve their interactions by learning to interpret, organize, and negotiate language and frames; this, in turn, can lead to better solutions through alternate communication methods and transformational learning.…”
Section: Importance Of Language In International Understandingmentioning
confidence: 99%
“…A person's literacy can influence a conflict-avoidant conversational style in the forms and cultural value of politeness, which can significantly impact how verbal and nonverbal language is used in interactions (Translation & Literary Studies et al, 2020). Language and politeness serve as a kind of consent (M. Eaton et al, 2022). It has the dual purpose of escalating conflicts and blaming the addressee, or it can reduce conflicts by avoiding opportunities to upset the interactants.…”
Section: Language As a Tool For Conflict Resolutionmentioning
confidence: 99%
“…NA faculty are consistently underfunded compared to their White colleagues in STEM. Recent studies have found systemic racial inequality in funding for all historically excluded groups including NA groups (Chen et al, 2022;Eaton et al, 2022). In 2019 alone, NSF received 20,400 research proposal submissions; only 99 of them came from self-identified NA researchers (.3%; Chen et al, 2022).…”
mentioning
confidence: 99%
“…This represents only .004% of the total number (n = 41,631) of funded research projects for this funding source (https://re port.nih.gov/nihdatabook/report/306; NIH Data Book-Report 306: Number of NIH Principal Investigators Funded by Grant Mechanism and Race). Other studies have highlighted that funding agencies have different conceptions of what constitutes fundable research, which leads to lack of funding as mentioned above (Eaton et al, 2022;Parker et al, 2018;Smith, 2021). Questions such as: What constitutes legitimate research?…”
mentioning
confidence: 99%